Canine obesity, overweight, and adipokine serum concentration are associated with hematological, biochemical, hormonal, and cardiovascular markers - Adrian Carzoli; Ana Meikle; Paula Pessina (Open Veterinary Journal)
Background: Canine obesity is an increasingly concerning issue that negatively impacts dogs' health, quality of life, and lifespan.